2015
DOI: 10.1038/srep16525
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution imaging with optical fluctuation using speckle patterns illumination

Abstract: Superresolution fluorescence microscopy possesses an important role for the study of processes in biological cells with subdiffraction resolution. Recently, superresolution methods employing the emission properties of fluorophores have rapidly evolved due to their technical simplicity and direct applicability to existing microscopes. However, the application of these methods has been limited to samples labeled with fluorophores that can exhibit intrinsic emission properties at a restricted timescale, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…In former work on fluctuating random pattern illumination by Kim et al 39 , the authors point out that achievable resolution enhancement with this technique depends on the size of the structures in the speckle pattern. In their work, diffraction limited illumination at a laser vacuum wavelength of 532 nm through a high NA 1.4 objective lens was used, resulting in speckle sizes in the illumination pattern down to λ/2NA = 190 nm.…”
Section: Supplementary Note 1: Obtainable Resolution For Waveguide-bamentioning
confidence: 99%
See 1 more Smart Citation
“…In former work on fluctuating random pattern illumination by Kim et al 39 , the authors point out that achievable resolution enhancement with this technique depends on the size of the structures in the speckle pattern. In their work, diffraction limited illumination at a laser vacuum wavelength of 532 nm through a high NA 1.4 objective lens was used, resulting in speckle sizes in the illumination pattern down to λ/2NA = 190 nm.…”
Section: Supplementary Note 1: Obtainable Resolution For Waveguide-bamentioning
confidence: 99%
“…Although original implementations of the fluctuation-based approaches SOFI and ESI use intrinsic quantum dot or fluorophore temporal intensity fluctuations (e.g. due to blinking and bleaching), it has recently been shown that speckle pattern illumination 38 can also invoke temporal emission fluctuations allowing for super-resolved fluctuation imaging 39 .…”
Section: Chip-based Fluctuation Imagingmentioning
confidence: 99%
“…Especially the evaluation of socalled cumulants of the speckle field illumination provides enhancements well beyond the Another interesting approach of using speckle illumination along with intensity correlations can be found in fluorescence microscopy. Here, Cho et al [78] showed that superresolution microscopy can be achieved with a practical enhancement factor of 1.6 over conventional widefield microscopy (when including deconvolution). Note that the difference to the approaches described in the above paragraphs lies in the incoherent response of fluorophores to a given illumination.…”
Section: Intensity Correlationsmentioning
confidence: 99%
“…Blinking fluorescence probes have been most commonly used, including fluorescent proteins (FPs) [21,27], organic dyes [28], quantum dots [15], and carbon nanodots [19]. Other types of optical fluctuations such as ones originating from diffusion of probes [29], FRET due to diffusion [30], and stochastic speckle illumination light [31] have also been exploited for SOFI imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Blinking fluorescence probes have been most commonly used, including fluorescent proteins (FPs) [21,27], organic dyes [28], quantum dots [15], and carbon nanodots [19]. Other types of optical fluctuations such as ones originating from diffusion of probes [29], FRET due to diffusion [30], and stochastic speckle illumination light [31] have also been exploited for SOFI imaging.Advantages of SOFI include compatibility with different imaging platforms and a wide variety of blinking probes, flexibility in imaging conditions [25], and a useful trade-off between spatial and temporal resolutions. SOFI has therefore the potential to democratized SR and be used in a wide variety of applications.…”
mentioning
confidence: 99%